Covid–19 and its implications on the mental health of selected Nigerian employees during the 2020 national lockdown - Abiodun Adekunle Ogunola; Moyosore Omodenuola Olupona (Universitas Negeri Yogyakarta, 2023)
The mental health of Nigerian employees in an organization is as important as their physical health at it allows them to focus on their jobs and aims at effective productivity in their organizations without any restrictions or restrains. A qualitative study approach was utilized through the use of structured interviews to explore the implications of Covid-19 on the mental health of those who worked from home and those who worked physically at their workplace. The study made use of 50 selected workers who worked at home and physically at work during the 2020 national lockdown in Nigeria. The study engaged the use of thematic analysis which led to the discussion of themes such as changes in work schedules, effects on mental capacity, exposure, adaptation, changes, and attitudes towards the lockdown. The study identified that there was a change in the mental health of Nigerian employees because they went through experiences that brought diverse perspectives to the way they view themselves and their work. It is recommended that people are equipped with psychological coping mechanisms to deal with unexpected situations and appreciate the significance of relationships with family, friends, colleagues at work, and speak up if they face any mental challenges.